2015
DOI: 10.1038/ctg.2015.31
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Sarcopenia Within MELD (MELD-Sarcopenia) and the Prediction of Mortality in Patients With Cirrhosis

Abstract: OBJECTIVES:Limitations of the Model for End-Stage Liver Disease (MELD) score include its failure to assess the nutritional and functional status of cirrhotic patients. Our objectives were to evaluate the impact of sarcopenia in cirrhosis and whether the inclusion of muscularity assessment within MELD could improve the prediction of mortality in patients with cirrhosis.METHODS:We included 669 cirrhotic patients who were consecutively evaluated for liver transplantation. Skeletal muscle index at the third lumbar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
324
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 300 publications
(353 citation statements)
references
References 31 publications
(42 reference statements)
22
324
1
6
Order By: Relevance
“…The outcome of this systematic review supports that sarcopenic liver transplant candidates face a worsened outcome. Besides the superiority of the MELD psoas area score of Durand et al to the MELD score and MELDNa score to predict waiting list mortality (15), the predictive value of the MELD sarcopenia score was found to be superior to the MELD score in a recent study (40). However, validation of these scores is recommended.…”
Section: Discussionmentioning
confidence: 97%
“…The outcome of this systematic review supports that sarcopenic liver transplant candidates face a worsened outcome. Besides the superiority of the MELD psoas area score of Durand et al to the MELD score and MELDNa score to predict waiting list mortality (15), the predictive value of the MELD sarcopenia score was found to be superior to the MELD score in a recent study (40). However, validation of these scores is recommended.…”
Section: Discussionmentioning
confidence: 97%
“…Studies have found that patients with significant sarcopenia (measured using the skeletal muscle index at the third lumbar vertebra) have worse pre-LT survival, and inclusion of sarcopenia into the MELD score may have value in predicting outcomes. (11,12) Furthermore, measures of frailty, such as activities of daily living, the Braden Scale, and the Morse fall risk score (standardized measures of frailty), have been found to be predictive of 90-day mortality, LOS, and need for rehabilitation for hospitalized patients with cirrhosis. (13) Additionally, markers of patient function, including the 6-minute walk test, (14) evaluation of maximum inspiratory pressure and maximum expiratory pressure using manometry, and surface electromyography of the diaphragm and rectus abdominis muscles, have shown that patients with cirrhosis have increased respiratory muscle weakness compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, because current methods used to assess liver disease severity, such as the Model for EndStage Liver Disease (MELD) score, do not give a functional assessment of the patient's fitness, we believe that the next step is to evaluate the development of composite scores, including new scores such as MELD-sarcopenia and MELD-psoas, 5,6 or to assign exemption points to those patients with sarcopenia so that they can undergo transplantation before they develop extreme sarcopenia. Nevertheless, this issue should be evaluated preferentially in prospective and multicenter controlled clinical trials.…”
mentioning
confidence: 99%